Eksistensi Perempuan Pada Manga Arte Karya Okubo Kei (Kajian Feminisme Eksistensial) - Farah Diva Salsabila; Diana Puspitasari; Muammar Kadafi (Universitas Diponegoro, 2023)
This research begins with several problems found around women, one of which is about gender equality. Because of these conditions, the research was conducted with the aim of knowing how women struggle in achieving their existence. The method used in this research is descriptive qualitative. This research data uses dialogues and pictures taken from the manga Arte as data sources. The data retrieval method used is a reading and note-taking technique. Data analysis techniques are presented descriptively. This study uses Simone de Beauvoir's existentialist feminism theory. The results of the study show that women because of their otherness often get injustice in gender relations. In order for women to gain their own existence, women must fight back by carrying out four strategies of self-transcendence according to Beauvoir, namely working, becoming an intellectual figure, working to achieve social transformation, and rejecting the other. Through research from Arte's manga, it can be concluded that a woman who wants to achieve her existence is not an easy thing to achieve. Women who want to get out of the shackles of patriarchy do not always get a positive response, and it takes more effort and hard work to achieve that existence. <a href=